ONLINE LEARNING BEST PRACTICES AND POSSIBLITIES - ABHISHEK JANI (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Its 21st century the century of science and technology new inventions are made daily The expansive nature of the Internet and the accessibility of technology have generated a surge in the demand for web based teaching and learning. Online education is quickly progressing into school districts and colleges across the nation. This paper trys to reflect how online education can be made more effective what are its advantages and disadvnatges. Educational institutions (schools, colleges, and universities) in India are currently based only on traditional methods of learning, that is, they follow the traditional set up of face-to-face lectures in a classroom. Although many academic units have also started blended learning, still a lot of them are stuck with old procedures. The sudden outbreak of a deadly disease called Covid-19 caused by a Corona Virus shook the entire world. The World Health Organization declared it as a pandemic. This situation challenged the education system across the world and forced educators to shift to an online mode of teaching overnight. The article includes the importance of online learning and Strengths, Weaknesses, Opportunities, & Challenges analysis of e-learning modes in the time of crisis.